The grey-zones of public-private surveillance: Policy tendencies of facial recognition for public security in Brazilian cities - André Ramiro; Lu\~a Cruz (Internet Policy Review, 2023)
The provision of biometric surveillance systems in cities' administration in Brazil is commonly delegated to private companies, where businesses supply facial recognition technologies (FRTs) to law enforcement entities. These public-private partnerships often manifest a lack of transparency, while counting on the legitimacy of the public administration to offer public services. These regulatory "grey-zones" affect smart city policies in Brazil, sidelining civil society and researchers, while narratives of efficiency push ahead the digitalisation of public services without proper safeguards. In Brazil, the collaborative work of civil society before the courts and government authorities has been the most successful path in halting FRTs in the area of public security, establishing strategic precedents that discursively focus on the "right to the city". This paper aims to achieve three goals: 1) shed light on these governance grey zones in order to identify the particularities of public-private models employed in the Brazilian socio-economic context; 2) examine the Brazilian human rights' organisations' attitudes towards the use of FRTs; and 3) provide a set of resilient principles that must guide biometric surveillance policies at the city level.
Keywords: 300; Facial recognition software; Security; Surveillance; Privacy; Brazil